A usnic acid-desonide co-crystal, preparation method and application thereof in preparations
Preparation of pineoxylic acid-desonide eutectic by solvent evaporation solves the problem of reduced solubility and dissolution of the drug, significantly improves its accumulated dissolution and permeability in vitro, and improves the bioavailability of the drug.
Patent Information
- Application Number
- CN202211247624.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-10-12
AI Technical Summary
Due to the increased lipophilicity of existing drug molecules, their solubility and dissolution are reduced, which in turn affects the efficacy and bioavailability.
Solyl acid-desonide eutectic was prepared by solvent evaporation. The main drug and ligand were carefully weighed, and after adding the solvent, stirring, filtering and drying, to obtain a co-crystal with improved solubility and dissolution.
The cumulative dissolution of pineoxylic acid-desonide eutectics was significantly improved in vitro. Compared with pineoxylic acid and desonide alone, the cumulative permeability of eutectics increased by 1.44 times, improving solubility, dissolution and permeability.
Smart Images

Figure CN116396254B_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a raw material of a pharmaceutical preparation, and more specifically relates to a usnic acid-desonide cocrystal, a preparation method and application thereof in a preparation. Background Art
[0002] Usnic acid is an antibiotic with a dibenzofuran structure. It is one of the most important and widely distributed lichen acids. It is mainly derived from plants of the genus Usnea. It is widely distributed in nature, has a high content, and has a wide range of pharmacological activities. In 1844, German scientist W. Knop first isolated usnic acid monomers from plants. In 1933, Curd and Robertson et al. first synthesized usnic acid artificially. As early as the 1960s, usnic acid was made into various dosage forms and widely used in the treatment of trauma, burns, chapped skin and other diseases. Due to its strong anti-inflammatory, antibacterial, anti-radiation, and anti-corrosion effects, it has been widely used in the pharmaceutical, perfume, cosmetics and other industries, and is added as a pure substance to toothpaste, mouthwash, deodorant, sunscreen and weight loss products.
[0003] Solubility and dissolution are key factors that determine the efficacy and activity of drugs. Early drug discovery research was based on traditional therapies or serendipitous discoveries. However, in the past two decades, the emergence of new diseases and the development of microbial resistance have called for the rational design and synthesis of drugs. Using advanced technologies such as high-throughput screening and combinatorial chemistry, many new drug targets have been identified, potential drug molecules have been synthesized, and their efficacy has been analyzed. Drug molecules discovered using these technologies are becoming larger and more lipophilic. Improving the solubility and dissolution of these lipophilic drug molecules without changing the molecular structure is a special challenge for the successful development of pharmaceutical products. The important role of cocrystals in improving the dissolution, solubility, and bioavailability of poorly water-soluble drugs. Some of the most important results show that cocrystals have remarkable solubility properties that are very different from those of the pure drug form. It can enable the drug to form crystals with other benign molecules or copolymers with specific stoichiometric compositions, thereby improving the solubility and dissolution of the drug. Summary of the invention
[0004] In order to achieve the technical purpose described in the background technology, the present invention provides a usnic acid-desonide cocrystal, wherein the main drug component of the usnic acid-desonide cocrystal is usnic acid, and the ligand component is desonide.
[0005] The stoichiometric ratio of usnic acid to desonide is 1-2:2-1.
[0006] The stoichiometric ratio of usnic acid to desonide is 2:1.
[0007] The solvent evaporation method is used to prepare usnic acid-desonide cocrystals.
[0008] The solvent evaporation method for preparing usnic acid-desonide cocrystal comprises the following steps:
[0009] 1) Accurately weigh the main drug UA and each ligand according to the stoichiometric ratio and add them to the reaction bottle;
[0010] 2) Add solvent, stir magnetically to dissolve, filter, and collect the filtrate in a vial;
[0011] 3) Evaporating to dryness at room temperature to obtain UA drug co-crystal.
[0012] Step 2) The solvent is dichloromethane.
[0013] Application of the usnic acid-desonide co-crystal in the preparation of antibacterial preparations.
[0014] Application of the usnic acid-desonide co-crystal in the preparation of anti-inflammatory preparations.
[0015] The claim relates to the use of usnic acid-desonide co-crystal in the preparation of skin wound repair preparations.
[0016] Application of the usnic acid-desonide co-crystal in the preparation of antibacterial preparations.
[0017] Application of the usnic acid-desonide co-crystal in the preparation of anti-inflammatory preparations.
[0018] The use of the usnic acid-desonide co-crystal in preparing a human wound repair preparation.
[0019] The beneficial technical effects of the present invention are: 1) The in vitro cumulative dissolution rate of usnic acid-desonide cocrystal is increased compared with that of UA and ligand; at 12h, the cumulative dissolution rate of usnic acid-desonide cocrystal is 6 times that of UA; the 24h cumulative permeability of usnic acid-desonide cocrystal is 1031.40±214.13μg / cm 2 Compared with UA 24h cumulative permeation, usnic acid-desonide cocrystal increased by 1.44 times; usnic acid-desonide cocrystal can improve solubility, dissolution and permeation;
[0020] 2) Compared with the positive control drug, usnic acid-desonide cocrystal can accelerate the healing process of the epidermis. At the same time, a small number of fibroblasts can be seen in the new dermis, and a large number of collagen fibers are tightly arranged. Skin appendages can also be seen, which are similar to the epidermis structure of normal skin, proving that usnic acid-desonide cocrystal promotes the wound repair process;
[0021] 3) Usnic acid-desonide cocrystal exerts an anti-inflammatory effect by inhibiting the secretion of pro-inflammatory factors IL-6 and TNF-α, thereby promoting wound repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Usnic acid structural formula;
[0023] Figure 2 Solvent screening;
[0024] Figure 3 UV spectrum of UA:D(1:1)EA sample;
[0025] Figure 4 UV spectrum of UA:D(1:1)Acetone sample;
[0026] Figure 5 UV spectrum of UA:D(1:1)DCM sample;
[0027] Figure 6 UV spectrum of UA:D(1:1)Chloroform sample;
[0028] Figure 7 UV spectrum of UA:D(2:1)EA sample;
[0029] Figure 8 UV spectrum of UA:D(2:1)Acetone sample;
[0030] Fig. 9 UV spectrum of UA:D(2:1)DCM sample;
[0031] Fig.10 UV spectrum of UA:D(2:1)Chloroform sample;
[0032] Fig.11 UV spectrum of UA:D(1:2)EA sample;
[0033] Fig.12 UV spectrum of UA:D(1:2)Acetone sample;
[0034] Fig.13 UV spectrum of UA:D(1:2)DCM sample;
[0035] Fig.14 UV spectrum of UA:D(1:2)Chloroform sample;
[0036] Fig.15 UA:D(1:1)Chloroform sample infrared spectrum;
[0037] Fig.16 UA:D(1:1)EA sample infrared spectrum;
[0038] Fig.17 UA:D(1:1)Acetone sample infrared spectrum;
[0039] Fig.18 UA:D(1:1)DCM sample infrared spectrum;
[0040] Fig.19 UA:D(2:1)Chloroform sample infrared spectrum;
[0041] Fig. 20 UA:D(2:1)EA sample infrared spectrum;
[0042] Fig.21 UA:D(2:1)Acetone sample infrared spectrum;
[0043] Fig. 22 UA:D(1:2)EA sample infrared spectrum;
[0044] Fig.23 UA:D(2:1)DCM sample infrared spectrum;
[0045] Fig.24 UA:D(1:2)Chloroform sample infrared spectrum;
[0046] Fig.25 UA:D(1:2)Acetone sample infrared spectrum;
[0047] Fig.26 UA:D(1:2)DCM sample infrared spectrum;
[0048] Fig. 27 XRD pattern of UA:D(1:2)EA sample;
[0049] Fig.28 XRD pattern of UA:D(1:1)EA sample;
[0050] Fig.29 XRD pattern of UA:D(2:1)Chloroform sample;
[0051] Fig.30 XRD pattern of UA:D2:1(DCM) sample;
[0052] Fig.31 Effect of pretreatment ball milling speed on particle size (n=3);
[0053] Fig.32 Effect of pretreatment ball milling time on particle size (n=3);
[0054] Fig.33 Effect of pretreatment liquid ratio on particle size (n=3);
[0055] Fig.34 UV spectrum of UA:D(2:1)DCM cocrystal;
[0056] Fig.35 UV spectrum of UA:D (2:1) cocrystal;
[0057] Fig.36 IR spectrum of UA:D(2:1)DCM eutectic;
[0058] Fig.37 IR spectrum of UA:D (2:1) cocrystal;
[0059] Fig.38 XRD pattern of UA:D(2:1)DCM eutectic;
[0060] Fig.39 UA:D (2:1) eutectic XRD pattern;
[0061] Fig.40 SEM images (A.UA; BD; C.UA:D2:1 mixture; D.DDCM eutectic);
[0062] Fig.41 SEM images (A.UA; BD; C.UA:D2:1 physical mixture; D.UA:D2:1 eutectic);
[0063] Fig.42 DSC-TGA curve of UA:D(2:1)DCM;
[0064] Fig.43 DSC-TGA curve of UA:D(2:1);
[0065] Fig.44 Solubility working curve of UA;
[0066] Fig.45 Solubility working curve of D;
[0067] Fig.46 Solubility working curve of UA:D2:1(DCM);
[0068] Fig.47 Solubility working curve of UA:D (2:1);
[0069] Fig.48 Solubility of usnic acid and UA:D2:1(DCM) cocrystal at different pH values;
[0070] Fig.49 Solubility of usnic acid and UA:D2:1 cocrystal at different pH values;
[0071] Fig.50 Dissolution curves of UA, ligands, and different UA cocrystals;
[0072] Fig.51Cumulative skin penetration rate of UA and UA:D2:1(DCM) cocrystal;
[0073] Fig.52 Schematic diagram of the microbroth method;
[0074] Fig.53 Growth curves of each bacteria;
[0075] Fig.54 Mouse body weight changes;
[0076] Fig.55 The wound conditions of mice in each group were treated with drugs for 14 consecutive days;
[0077] Fig.56 HE staining results of the wounds of mice in each group;
[0078] Fig.57 The levels of IL-10 in serum of each group;
[0079] Fig.58 The levels of IL-6 in serum of each group;
[0080] Fig.59 The levels of TNF-α in serum of each group. DETAILED DESCRIPTION
[0081] Example 1 Preparation of Usnic Acid Cocrystals by Solvent Evaporation
[0082] The present invention aims to develop a skin topical preparation, with the goal of improving the solubility and percutaneous permeability of the drug and enhancing the antibacterial and anti-inflammatory effects. When designing UA cocrystals, the main considerations are the hydrogen bonding rules and the difficulty of forming synthons between functional groups. According to the molecular structure of usnic acid ( Figure 1 ), there is -OH, which can form hydrogen bonds with functional groups such as -C=O. At the same time, combined with the research purpose and objectives of the subject, qualified drugs are screened in the compound library as ligands, and subsequent ligand types, reaction solvents, and reaction ratios are screened.
[0083] 1. Preparation method of UA eutectic
[0084] The co-crystal was prepared by solvent evaporation method. The main drug UA and each ligand were accurately weighed according to the stoichiometric ratio and added to the reaction bottle, and the same volume of different solvents were added respectively. After sufficient magnetic stirring and dissolution, the filtrate was collected in a penicillin bottle and evaporated to dryness at room temperature to obtain UA drug co-crystal.
[0085] 2. Screening of solvents for eutectic formation
[0086] The drug has a certain solubility in the solvent, which can increase the collision between drug molecules and improve the possibility of drug cocrystal formation. Based on the preliminary experiment, the cocrystal was prepared by solvent evaporation. The UA cocrystal was prepared by fixing the stoichiometric ratio of UA to ligand to 1:1, the solvent volume to 10 mL, and the magnetic stirring time to 30 min, and the optimal reaction solvent was screened.
[0087] 3. Screening of drug-ligand ratio
[0088] The selected optimal reaction solvent was fixed, and UA and each ligand with a stoichiometric ratio of 1:1, 1:2, and 2:1 were weighed respectively. The solvent volume was 10 mL, and the magnetic stirring time was 30 min. UA cocrystals were prepared by the solvent reaction method to screen the optimal ratio of drug and ligand.
[0089] 4. Determination of reaction solvent
[0090] Based on preliminary experiments, the UA-ligand stoichiometric ratio was fixed at 1:1 and the cocrystal was prepared by solvent evaporation. Figure 2 .
[0091] Experimental phenomenon Figure 2 The results showed that anhydrous ethanol, isopropanol, and methanol solvents had poor solubility for UA and ligand drugs, and it was difficult to obtain the product. Therefore, ethyl acetate (EA), acetone (Acetone), dichloromethane (DCM), and chloroform (Chloroform) were finally selected as solvents for subsequent screening of the ratio of UA to ligand.
[0092] 5. Screening and evaluation indicators of UA eutectic samples
[0093] (1) Ultraviolet (UV) analysis
[0094] 1.0 mg of UA API and each cocrystal sample were accurately weighed, dissolved in anhydrous ethanol and fixed to volume to obtain 10 μg mL -1 Sample solution. Scan at 200-400 nm, import the data into Origin8.0 for processing, and draw the UV map of each sample.
[0095] According to the UV spectra of each UA eutectic, the UV absorption differences of UA, ligand, UA-D mixture and UA eutectic samples were compared. The results are as follows Figure 3-Figure 14 .
[0096] Depend on Figures 3 to 6 It can be seen that compared with the mixture of UA, D, and EA, the UA:D1:1 reaction has two absorption peaks, the maximum absorption wavelength shifts to the left at 234nm, and the absorption intensity is significantly enhanced ( Figure 3); The UA:D1:1 in Acetone has an obvious absorption peak, the maximum absorption shifts to the left at 236nm, and the absorption intensity is significantly enhanced ( Figure 4 ); UA:D1:1 reacted in DCM has two absorption peaks, and the maximum absorption shifts to the left at 234nm. The absorption intensity at this wavelength is slightly higher than that of UA, ligand, and UA:D1:1 ( Figure 5 ); The UA:D1:1 in Chloroform has two absorption peaks, the maximum absorption shifts to the left at 234nm, and the absorption intensity is significantly enhanced ( Figure 6 ), it is judged that UA:D1:1(EA) and UA:D1:1(Chloroform) are likely to form eutectic.
[0097] Depend on Figures 7-10 It can be seen that compared with UA, D, and mixed materials, the UA:D2:1 reacted in EA has two absorption peaks, and the maximum absorption wavelength shifts to the left at 234nm, and the absorption intensity is higher than that of UA and ligand D ( Figure 7 ); The UA:D2:1 in Acetone has an obvious absorption peak, and the maximum absorption shifts to the left at 236nm, and the absorption intensity is higher than that of UA and ligand D ( Figure 8 ); UA:D2:1 reacted in DCM has an absorption peak, and the maximum absorption shifts to the left at 234nm. The absorption intensity at this wavelength is significantly greater than that of UA and ligand ( Fig. 9 ); UA:D2:1 in Chloroform has two absorption peaks, the maximum absorption shifts to the left at 234nm, and the absorption intensity is slightly enhanced ( Fig.10 ), it is judged that UA:D2:1(EA), UA:D2:1(DCM), and UA:D2:1(Chloroform) are likely to form eutectics.
[0098] Depend on Figures 11 to 14 It can be seen that compared with UA, D, and mixed materials, the UA:D1:2 in the EA reaction has an absorption peak, the maximum absorption wavelength shifts left to 236nm, and the absorption intensity is significantly enhanced ( Fig.11 ); The UA:D1:2 in Acetone has an obvious absorption peak, and the maximum absorption shifts to the left at 236nm, which is similar to the physical mixture, only the absorption intensity is slightly higher ( Fig.12 ); UA:D1:2 reacted in DCM has an absorption peak, and the maximum absorption shifts left to 234nm. The absorption intensity at this wavelength increases significantly ( Fig.13 ); UA:D1:2 in Chloroform has two obvious absorption peaks, the maximum absorption shifts to the left at 232nm, and the absorption intensity increases significantly ( Fig.14 ), it is judged that UA:D1:2(EA) and UA:D1:2(Chloroform) are likely to form eutectic.
[0099] (2) Infrared (IR) analysis
[0100] Fourier transform infrared spectrometer (FT-IR Spectrometer) is used as a supplementary means to prove the formation of cocrystals. Accurately weigh appropriate amounts of UA raw materials and each cocrystal sample at 400-4000 cm -1 The data were scanned within a wavelength range, and the data were imported into Origin8.0 for processing, and infrared images of each sample were obtained.
[0101] Different eutectic samples of usnic acid were collected at 4000-400 cm -1 Perform a range infrared scan, record the spectrum data, and import the data into Origin8.0 for processing to compare the infrared differences of UA, D, UA-D physical mixture, and usnic acid eutectic samples. The results are shown in the figure.
[0102] Depend on Figures 15 to 18 It can be seen that the absorption intensity of each characteristic peak of UA:D1:1(EA) is weakened, and the absorption intensity of each characteristic peak of UA:D1:1(EA) is weakened. -1 、1709cm -1 A peak appears at 1612cm -1 The peak at the center is sharper; the infrared of UA:D1:1(Acetone) is similar to UA, only the intensity is weakened; UA:D1:1(DCM) is similar to ligand D and the intensity has no obvious change; the characteristic peak of UA:D(1:1)Chloroform is similar to UA:D(1:1), judging that UA:D1:1(EA) eutectic has formed.
[0103] Depend on Figures 19 to 22 It can be seen that the absorption intensity of each characteristic peak of UA:D2:1(EA) is weakened, and there is almost no difference with UA:D(2:1) mixture; UA:D(2:1) Acetone infrared is similar to UA, only the intensity is weakened; UA:D2:1(DCM) 3100~2800cm -1 The peak at 1706cm -1 -C=O and 1265cm -1 、1046cm -1 The sharp peak at 1655cm -1 The peak intensity at 3021cm is significantly weakened; UA:D(2:1)Chloroform at 3021cm -1 The characteristic peak shifted to 3010cm -1 There are slight changes in the fingerprint region, indicating that UA:D2:1(DCM) and UA:D(2:1)Chloroform eutectics have been formed.
[0104] Depend on Figures 23-26It can be seen that the absorption intensity of each characteristic peak of UA:D1:2(EA) is weakened, and the absorption intensity of each characteristic peak of UA:D1:2(EA) is weakened. -1 The characteristic peak shifted to 3093cm -1 The infrared spectrum of UA:D1:2(Acetone) is similar to that of UA:D2:1 mixture, and the intensity is equivalent; the characteristic peak positions of UA:D1:2(DCM) and UA:D1:2(Chloroform) cocrystals are similar to those of ligand D, and the intensity is weakened, indicating that UA:D1:2(EA) cocrystal is formed.
[0105] According to the UV results of different usnic acid eutectic samples, the maximum absorption peaks and absorption intensity changes of each group at the same concentration were compared; according to the infrared results, the characteristic peak positions and fingerprint areas of the hydroxyl and carbonyl groups of each group were compared, and 4 samples that may form usnic acid eutectics were screened out for the next step of verification.
[0106] (3) X-ray diffraction (XRD) analysis
[0107] The XRD pattern was detected by BRUKER D8 Advance X-ray diffractometer, the emission target was Cu Ka target, the tube voltage and current were 40 kV and 30-40 mA respectively, and the scanning rate was 1°·min -1 The samples were scanned at an angle of 2 to 60° with a scanning step of 0.02°. The data were recorded and imported into Origin 8.0 for processing to obtain the X-ray diffraction patterns of each sample.
[0108] After UV and IR identification and testing, the UV and IR spectra of each group of samples were compared, and 24 different usnic acid eutectic samples were preliminarily screened out. Then, the X-ray diffraction method was used to compare the diffraction peak differences of 24 different usnic acid eutectics at 2-60°, and the data was recorded. After the data was imported into Origin8.0 for processing, the XRD spectrum was obtained. Figure 25-28 .
[0109] Depend on Fig. 27 It can be seen that the peak intensity of UA is weak, and the main diffraction peaks include 10.3° and 12.8°. The diffraction peak intensity of ligand D is large, and the main diffraction peaks are 14.2° and 21.3°. The diffraction peaks of UA:D2:1EA overlap with those of ligand D, and the intensity is slightly weakened. Fig.28 It can be seen that the diffraction peaks of UA:D1:2EA overlap with those of ligand D, and the intensity is slightly weakened; Fig.29 It can be seen that the diffraction peaks of UA:D(2:1)Chloroform overlap with ligand D, and the main peak intensity is enhanced; Fig.30 It can be seen that compared with UA and ligand D, the two main peaks at 12.8° and 14.2° of UA:D2:1(DCM) disappeared, and a new main peak appeared at 10.2°, which was shifted and the intensity was significantly weakened.
[0110] By combining UV, IR and XRD identification methods, UA:D2:1 (DCM) was finally screened out.
[0111] Example 2 Preparation of usnic acid eutectic by ball milling and high pressure homogenization
[0112] The preparation of certain drug cocrystals by solvent reaction method requires the use of organic solvents or even Class II solvents. Ball milling and high-pressure homogenization are new formulation technologies that are currently widely used in the pharmaceutical field. Based on environmental considerations, the preparation of cocrystals by combining ball milling and high-pressure homogenization can avoid the use of organic solvents. At the same time, under appropriate parameter conditions, the high-pressure homogenization method has the advantage of making the sample particle size reach the nanometer level. It is planned to use ball milling-high-pressure homogenization method to prepare UA cocrystals. Based on the preliminary experiment, purified water was used as the dispersing solvent, and after pretreatment by ball milling, UA cocrystals were homogenized by a high-pressure homogenizer.
[0113] The ball milling method and high-pressure homogenization method are combined to carry out process screening and optimization of the method, with particle size as the indicator and ball milling speed, ball milling time, drug-liquid ratio and high-pressure homogenization pressure and times as the factors.
[0114] 1. Screening of pretreatment conditions for ball milling
[0115] (1) Effect of ball mill speed on particle size
[0116] Weigh appropriate amounts of UA and ligand, mix them, add 20 mL of purified water, and place them in a ball mill. The ball milling time is fixed at 1 h, and the ball mill speed is set at 350, 400, 450, 500, 550, and 600 r·min. -1 After the reaction is completed, the reaction solution is taken out and diluted 100 times, and the particle size is measured. The measurement is repeated three times, and the data is recorded. The rotation speed is used as the horizontal axis and the particle size is used as the vertical axis. The optimal rotation speed is selected using the particle size as an indicator.
[0117] The experimental results are shown in Table 1.4, with rotation speed as the horizontal axis and particle size as the vertical axis, and Origin 8.0 was used to draw the graph, as shown in Table 1.4. Fig.31 The condition of the smallest particle size was selected, and the optimal rotation speed of UA:D (2:1) eutectic was preferably 550 r / min.
[0118] Table 1.4 Effect of ball milling speed on particle size (n=3)
[0119]
[0120] (2) Effect of ball milling time on particle size
[0121] Weigh appropriate amounts of UA and ligand, mix them, add 20 mL of purified water, fix the speed, and set the ball milling time to 0.5 h, 1 h, 1.5 h, 2 h, and 2.5 h. After the reaction is completed, remove the reaction solution and dilute it 100 times. Measure the particle size. Parallel measurement is performed 3 times. Record the data and plot it with time as the horizontal axis and particle size as the vertical axis using Origin 8.0. Use particle size as an indicator to screen the optimal time.
[0122] The experimental data are shown in Table 1.5, with time as the horizontal axis and particle size as the vertical axis, and Origin8.0 was used to draw the graph, as shown in Table 1.5. Fig.32 The condition of the smallest particle size was selected, and the optimal time for obtaining the UA:D (2:1) eutectic was 1 h.
[0123] Table 1.5 Effect of ball milling time on particle size (n=3)
[0124]
[0125] (3) Effect of drug solution mass-volume ratio on particle size
[0126] Fix the optimal speed and time, take appropriate amount of UA and ligand, add purified water in the ball mill according to the mass volume ratio of 1:2, 1:5, 1:10, 1:15, 1:20, and place in the ball mill. After the reaction is completed, take the reaction solution and dilute it 100 times, measure the particle size, measure it in parallel 3 times, record the data, and plot it with Origin 8.0 with the speed as the horizontal axis and the particle size as the vertical axis. Use the particle size as an indicator to screen the optimal speed.
[0127] The experimental data are shown in Table 1.6, with the drug-liquid ratio as the horizontal axis and the particle size as the vertical axis, and Origin8.0 was used to draw the graph, as shown in Fig.33 The condition of the smallest particle size was selected, and the optimal solution mass volume ratio of UA:D (2:1) eutectic was preferably 1:10.
[0128] Table 1.6 Effect of drug-liquid ratio on particle size (n=3)
[0129]
[0130] (4) Verification of the optimal pretreatment process
[0131] According to the optimal pretreatment process, three UA eutectics were prepared in parallel, the particle size was measured and the RSD was calculated to verify the pretreatment preparation process conditions.
[0132] According to the optimal pretreatment process conditions obtained by optimization, UA:D (2:1) eutectics were prepared in parallel for 3 batches. The particle size of each batch of eutectics was measured to be 278.28±4.7748, the particle size distribution index (PDI) was 0.1379±0.0253, and the RSD% was 1.72% and 3.22%, which proved that the pretreatment preparation process obtained by experimental screening was reliable, as shown in Table 1.7.
[0133] Table 1.7 Verification results of the best pretreatment process (n=3)
[0134] verify 1 2 3 Mean ± SD RSD(%) Average particle size (nm) 271.69 280.29 282.86 278.28±4.7748 1.72 Particle Size Distribution Index (PDI) 0.1497 0.1613 0.1027 0.1379±0.0253 3.22
[0135] In summary, when the ball milling speed of UA:D (2:1) eutectic was 550 r / min, the ball milling time was 1 h, and the drug-liquid ratio was 1:10, the particle size of the obtained sample was optimal and verified.
[0136] 2. Optimization of process conditions for preparing usnic acid eutectics by high pressure homogenization
[0137] (1) Orthogonal optimization experiment
[0138] Orthogonal experimental design was used to optimize the high-pressure homogenization process of UA:D (2:1) eutectic. The experimental factors and levels of UA:D (2:1) eutectic were determined based on preliminary experiments and single-factor investigations. SPSS Statistics 26 software was run, and the SPSSStatistics data editor was entered. Click on the orthogonal design in the data. Factor A is the high-pressure homogenization pressure, and factor B is the number of high-pressure homogenizations. An orthogonal experimental design table was generated, as shown in Table 1.3. The particle size was used as an indicator, and the quadratic statistical method was used to calculate the score. The best process was selected based on the minimum number of occurrences of the particle size indicator.
[0139] Table 1.3 Orthogonal test table
[0140]
[0141] (2) Best process verification experiment
[0142] UA:D (2:1) eutectics were prepared according to the best preparation process conditions obtained after star-point response surface optimization. The particle size was examined and the predictive performance of the mathematical model was examined using the relative error between the measured value and the predicted value [(predicted value - true value) / predicted value × 100%].
[0143] 1) Single variable method screening conditions
[0144] The results obtained for different high-pressure homogenization pressures and the corresponding homogenization times are shown in Tables 1.8 and 1.9.
[0145] Table 1.8 Effect of high pressure homogenization conditions on particle size (n=3)
[0146]
[0147] Table 1.9 Effect of high pressure homogenization conditions on PDI (n=3)
[0148]
[0149] Through direct analysis, it can be seen that when the pressure is 50bar, 100bar, 150bar, and the homogenization is 9, 11, and 13 times, the change trend and data of the average particle size are the most representative, and the PDI value shows that the obtained sample distribution is relatively uniform. Therefore, three levels of the two factors of pressure and number are selected, and the average particle size is used as an indicator to design an orthogonal optimization experiment.
[0150] 2) Orthogonal test results
[0151] The orthogonal experiment results are shown in Table 1.10.
[0152] Table 1.10 Orthogonal test results
[0153]
[0154] Table 1.11 The number of occurrences of the minimum index at the corresponding level of each factor
[0155]
[0156] From the intuitive analysis of Table 1.10, it can be seen that when the number of levels of A and B is 2, the average particle size measured is the smallest, which is 139.33nm, that is, Scheme A 2 B 2 The best. Through calculation, first find the sum of the indicators corresponding to factors A and B at the same level, recorded as K 1 , K 2 , K 3 ; Then calculate their arithmetic means, and then calculate the range of the arithmetic means. The larger the range, the more important the factor, and RA>RB, so it is confirmed that high-pressure homogenization pressure is the main influencing factor. According to the quadratic statistical method, the corresponding indicators of the two factors at different levels are compared. The number of occurrences of the minimum indicator at the corresponding level of each factor in the summary table is shown in Table 1.11. It can be seen from the table that in the most ideal indicator data, the 2-level of factor A appears the most times, while the 3-level of factor B appears the most times. The optimal solution is A. 2 B 3 . Compared with the scheme A obtained by direct observation and calculation 2 B 2 Different. Through comparison and verification, we get solution A 2 B 3 and Plan A 2 B 2The average particle sizes are 144.69nm and 138.45nm respectively, so the best solution is A 2 B 2 , that is: homogenization pressure 150bar, homogenization times 9 times.
[0157] 3) Validation experiment
[0158] Three batches of UA:D (2:1) eutectics were prepared in parallel according to the optimal process conditions, and the experimental results are shown in Table 1.12. The data analysis results show that the average particle sizes were 140.25 nm, 139.20 nm, and 145.03 nm, respectively, and the particle size distribution indexes were 0.1487, 0.1613, and 0.1027, of which the RSD% of the average particle size was 1.79%, and the PDI was less than 0.2, with uniform distribution, proving that the preparation process obtained by the orthogonal experiment is reliable.
[0159] Table 1.12 Process verification experiment (n=3)
[0160]
[0161] In summary, UA:D (2:1) eutectic was prepared by ball milling-high pressure homogenization. The optimal preparation process conditions of UA:D2:1 eutectic are: ball milling speed 500r·min -1 , ball milling time 1h, drug solution mass volume ratio 1:2, high pressure homogenization pressure 150bar, homogenization times 9 times, and finally nano-scale UA:D (2:1) eutectic was obtained.
[0162] Example 3 Investigation of the Characterization of Usnic Acid Cocrystals
[0163] The UA:D (2:1) cocrystals prepared in Examples 1 and 2 were used as the analysis objects. Four groups of samples, namely UA, ligand, UA:D (2:1) mixture and UA:D (2:1) cocrystal, were analyzed by UV, FT-IR, XRD, SEM and TGA-DSC to characterize the usnic acid cocrystals.
[0164] 1. Ultraviolet-visible spectrophotometry (UV) analysis
[0165] Four groups of samples, including UA, ligand, UA:D (2:1) physical mixture and UA:D (2:1) cocrystal, were prepared with 10 μg / mL solutions respectively. The full wavelength of 200-400 nm was scanned to obtain the UV full wavelength results. The data were imported into Origin8.0 for processing and the UV spectra of usnic acid, ligand, physical mixture and different usnic acid cocrystal samples were compared.
[0166] Fig.34Among them, D has only one absorption peak with a maximum absorption wavelength of 244nm; the maximum absorption wavelength of UA:D (2:1) mixture is 230nm; UA:D2:1 (DCM) has only one absorption peak with a maximum absorption wavelength of 234nm, and the ultraviolet absorption intensity at this wavelength is higher than that of UA, D, and UA:D (2:1) mixture.
[0167] Fig.35 In the figure, the UV scanning spectra of UA, ligand, UA:D (2:1) physical mixture and UA:D (2:1) at the same concentration in the range of 200-400nm are compared. The full wavelength curve of UA has two absorption peaks, and the maximum absorption wavelength is 286nm; the ligand drug D has only one absorption peak, and the maximum absorption wavelength is 244nm; the maximum absorption wavelength of the physical mixture in the same proportion is 230nm; the UA:D (2:1) cocrystal has only one absorption peak, and the maximum absorption wavelength is 242nm. The UV absorption intensity at this wavelength is lower than that of UA and physical mixture, but higher than that of D.
[0168] 2. Infrared spectroscopy (FT-IR) analysis
[0169] Four groups of sample powders of UA, ligand, UA:D (2:1) mixture and UA:D (2:1) eutectic were obtained at 400-4000 cm -1 The wavelength range was scanned to obtain the spectrum and data, which were analyzed using Origin8.0 software. Fig.36 Compared with UA, D, and UA:D2:1 mixture, UA:D2:1 (DCM) has a peak concentration of 3100-2800 cm -1 The peak at 1706cm -1 The -C=O at 1655cm -1 The peak intensity at 1265cm -1 The sum of 1046cm -1 The sharp peak at 100% disappeared. The differences in the spectra of each group were found based on the infrared peaks, indicating that UA eutectic was formed.
[0170] Fig.37 1690.5cm in UA -1 The stretching vibration peak of C=O belongs to the stretching vibration peak of the keto carbonyl C=O in D, and the wave number is 1709cm -1 UA:D2:1 mixture appears at 1690cm -1 and 1709cm -1 Both wave numbers belong to the stretching vibration peak of C=O, but the absorption peak in UA-D (2:1) eutectic undergoes an obvious red shift to the low frequency direction to 1653.5 cm -1In contrast, the stretching vibration absorption peak of -OH in UA:D(2:1) is blue-shifted, broadened and enhanced. It can be inferred that C=O and -OH in UA:D(2:1) form a hydrogen bond, indicating the formation of UA eutectic.
[0171] 3. X-ray diffraction (XRD) analysis
[0172] Four groups of samples, UA, ligand, UA:D (2:1) mixture and UA:D (2:1) eutectic, were subjected to X-ray diffraction (XRD) analysis. The detection conditions were as follows: the emission target was Cu Ka target, the tube voltage and current were 40 kV and 30-40 mA, respectively, and the scanning rate was 1°·min -1 The sample was scanned at an angle of 2 to 60° with a scanning step of 0.02°, and the diffraction patterns were processed using Origin 8.0 software. Fig.38 Compared with UA, D, and UA:D2:1 physical mixtures, the diffraction peak of UA:D2:1 (DCM) at 14.2° is significantly weakened, the overall diffraction peaks are weakened, the main peak becomes the diffraction peak at 10.4°, and the diffraction peaks at many other locations are weakened or even disappear, proving the formation of a new crystal form. Therefore, it is judged that usnic acid drug cocrystal is produced.
[0173] See Fig.39 Compared with UA, D, and physical mixture, it is obvious that the diffraction peak of UA:D (2:1) cocrystal at 14.2° is significantly weakened, the overall diffraction peaks are weakened, the main peak becomes the diffraction peak at 10.4°, and the diffraction peaks at other locations are weakened or even disappear, proving that a new crystal form is produced. Therefore, it is judged that usnic acid drug cocrystal is produced.
[0174] 4. Scanning electron microscopy analysis (SEM)
[0175] Appropriate amounts of each sample were weighed and dispersed on coverslips, gold-plated and fixed on copper plates. The surface morphology of the electrosprayed samples was evaluated using a scanning electron microscope at 10 kV.
[0176] like Fig.40 It was found that usnic acid was columnar and blocky crystals, most of which were blocky with larger particle size; D was clustered crystals with a smooth surface; the prepared UA:D2:1 (DCM) was short columnar crystals with obvious changes in morphology, so it was judged that UA eutectic was formed.
[0177] like Fig.41The scanning electron microscopy results of UA raw material, D, UA:D2:1 physical mixture and UA:D (2:1) cocrystal were significantly different. UA was columnar and blocky crystals with larger particle size; D was clustered crystals, and UA:D2:1 physical mixture was a superposition of the morphologies of UA and D; the prepared UA:D (2:1) cocrystal had a more regular shape, uniform distribution, and significantly reduced particle size, indicating that UA cocrystal was formed.
[0178] 5. Thermogravimetric-differential scanning calorimetry (TGA-DSC)
[0179] The DSC spectra were measured by using a Mettler TGA / DSC1 / 1600HT instrument. The samples for DSC analysis were placed in a crucible and scanned from 30°C to 800°C at a heating rate of 10°C / min under a nitrogen flow of 50 mL / min. Origin 8.0 software was used for preliminary analysis and evaluation of the spectra.
[0180] Depend on Fig.42 It can be seen that the melting point of UA:D2:1 (DCM) is 183.5℃, which is significantly lower than that of UA (199℃), D (276.5℃) and UA:D (2:1) mixture (194℃). Under nitrogen atmosphere test conditions, the initial weight loss temperature of UA is 272℃, and the weight loss is 61.3% at 313℃; the initial weight loss temperature of D is 378℃, and the weight loss is 90.4% at 398℃; the UA:D2:1 mixture starts to lose weight at 351.7℃, and loses 81.9% at 358.9℃; UA:D2:1 (DCM) starts to lose weight at 220℃, and loses 75.1% at 368℃. This shows that the skeleton of UA:D2:1 (DCM) eutectic is relatively stable before 220℃, and it is also a new substance with unique thermal properties different from API and CCF, judging that UA eutectic is formed.
[0181] Depend on Fig.43 It can be seen that the melting temperature of UA:D (2:1) eutectic is 190℃, which is significantly lower than the melting temperatures of UA (199℃), D (276.5℃) and UA:D (2:1) mixture (194℃). Under nitrogen atmosphere test conditions, the initial weight loss temperature of UA is 272℃, and the weight loss is 61.3% at 313℃; the initial weight loss temperature of D is 378℃, and the weight loss is 90.4% at 398℃; UA:D 2:1 mixture starts to lose weight at 351.7℃, and loses 81.9% at 358.9℃; UA:D (2:1) eutectic starts to lose weight at 245.5℃, and loses 73.56% at 800℃. This shows that the skeleton of UA:D (2:1) eutectic is relatively stable before 245.4℃, and it is also a new substance with unique thermal properties different from API and CCF, judging that UA eutectic is formed.
[0182] Example 4 Analysis of the physicochemical properties of usnic acid-desonide co-crystals
[0183] 1. Solubility determination
[0184] 1) Preparation of solutions with different pH values
[0185] ①pH 1.2 solution: Measure 8.3mL of hydrochloric acid (36.5%) into a volumetric flask, add purified water, mix and make up to 1000mL, shake well.
[0186] ②pH 2.0 buffer solution: Solution A: Measure 16.6 mL of phosphoric acid into a volumetric flask, add purified water to make up to 1000 mL, and shake well; Solution B: Weigh 71.63 g of disodium hydrogen phosphate into a volumetric flask, add purified water to dissolve, and make up to 1000 mL, and shake well; Take 725 mL of Solution A and 275 mL of Solution B and mix well.
[0187] ③ pH 3.0 buffer: Solution A: Weigh 35.61 g of disodium hydrogen phosphate dodecahydrate into a volumetric flask, add water to dissolve and dilute to 1000 mL to obtain 0.2 mol·L -1 Disodium hydrogen phosphate solution; Solution B: weigh 21.01 g of citric acid monohydrate into a volumetric flask, add water to dissolve and dilute to 1000 mL to obtain 0.1 mol·L -1 Citric acid solution: Take 205.5mL of liquid A and 794.5mL of liquid B, mix and shake well.
[0188] ④pH 4.0 buffer: 0.2 mol·L -1 Disodium hydrogen phosphate solution 385.5 mL, 0.1 mol·L -1 Add 614.5 mL of citric acid solution and shake well to obtain the product.
[0189] ⑤ pH 5.0 buffer: 0.2 mol·L -1 Disodium hydrogen phosphate solution 515 mL, 0.1 mol·L -1 485mL of citric acid solution, shake well to obtain.
[0190] ⑥ pH 6.8 buffer: Solution A: weigh 27.2170 g potassium dihydrogen phosphate into a volumetric flask, add purified water to make up to 1000 mL, and shake to obtain 0.2 mol·L -1 Potassium dihydrogen phosphate solution; Solution B: weigh 8.0 g of sodium hydroxide into a volumetric flask, add purified water to dissolve, and dilute to 1000 mL. Shake well to obtain 0.2 mol·L -1 Sodium hydroxide solution: Take 250mL of solution A and 118mL of solution B, dilute with water and make up to 1000mL, shake well.
[0191] ⑦pH 7.2 buffer: 0.2 mol·L -1 250mL of potassium dihydrogen phosphate solution and 0.2mol·L -1 Mix 175mL of sodium hydroxide solution, add purified water to dilute and make up to 1000mL, and shake well.
[0192] 2) Establishment of working curve
[0193] ① Preparation of UA and ligands Q and D solutions: Accurately weigh 10 mg of UA, Q, and D into a 100 mL volumetric flask, add water to prepare UA, Q, and D solutions with a concentration of 0.1 mg·mL, and dilute to 20, 18, 16, 14, 12, 10, 8, and 4 μg·mL -1 For a series of solutions, measure the absorbance values and draw a standard curve with concentration as the horizontal axis and absorbance ABS as the vertical axis.
[0194] ② Preparation of UA eutectic solution: Accurately weigh 10 mg of UA:Q1:1 (EA), UA:Q1:1 (DCM), UA:D2:1 (DCM), UA:Q2:1 (Acetone), UA:Q (1:1), and UA:D (2:1) in a 100 mL volumetric flask, and add water to a concentration of 0.1 mg mL -1 The solution was diluted to 20, 18, 16, 14, 12, 10, 8, and 4 μg mL -1 For a series of solutions, measure the absorbance values and draw a standard curve with concentration as the horizontal axis and absorbance ABS as the vertical axis.
[0195] ③Methodological validation
[0196] (1) Precision study
[0197] Take the lower (4μg·mL -1 ), medium (12 μg·mL -1 ), high (16 μg·mL -1 ) Three concentrations of UA solutions were detected 5 times at 288nm UV, and their absorbance values were recorded and the precision was calculated.
[0198] (2) Reproducibility study
[0199] Prepare 6 copies of 6 μg mL in parallel -1 The UA bulk drug sample solution was detected under UV light at 288 nm, and its absorbance value was recorded and the RSD value was calculated.
[0200] (3) Stability study
[0201] Take the same UA reference solution, detect it under UV light at 288 nm at 0 h, 2 h, 4 h, 8 h, 12 h, and 24 h, record its absorbance value, and calculate the RSD value.
[0202] (4) Sample recovery study
[0203] Accurately measure the known content of the raw material sample solution (12μg·mL -1 )5mL was placed in a 10mL volumetric flask, for a total of 9 portions. Each of the 3 portions was accurately added to a concentration of 12μg·mL -1 4mL, 5mL, and 6mL of the reference solution are equivalent to 80%, 100%, and 120%, for a total of 9 portions. They are detected at 288nm UV, and their absorbance values are recorded to calculate the average recovery rate. The recovery rate is calculated according to the formula: Recovery rate (%) = (CA) / B×100%. (C is the measured value, B is the amount of reference added, and A is the amount of the measured component contained in the test sample)
[0204] ① Establish the dissolution working curves of UA, D, UA:D2:1 (DCM), and UA:D (2:1) in purified water. The linear regression equation is shown in Table 3.3. The Excel plot is shown in Figures 44 to 46 .
[0205] Table 3.3 Solubility working curve
[0206]
[0207]
[0208] ②The precision results are recorded in Table 3.4. The RSDs are all less than 2.0%. The precision meets the requirements, indicating that this method is feasible.
[0209] Table 3.4 Precision results (n=5)
[0210]
[0211] ③The repeatability results are recorded in Table 3.5. The calculated RSD value of the repeatability experimental results is 2.29%, indicating that the repeatability is good and meets the requirements.
[0212] Table 3.5 Repeatability results (n=6)
[0213]
[0214] ④ The results of the stability study are recorded in Table 3.6. The calculated RSD value is 1.82%, indicating that the sample solution is relatively stable within 24 hours.
[0215] Table 3.6 Stability test (n=6)
[0216]
[0217] ④ The sample recovery rate results are recorded in Table 3.7. The average sample recovery rate of UA is 2.45%, and the calculated RSD value is 2.45%<3%, indicating that the accuracy of this method meets the requirements.
[0218] Table 3.7 Sample recovery experiment (n=9)
[0219]
[0220]
[0221] 3) Determination of solubility
[0222] Weigh excess UA, D, UA:D2:1 (DCM), and UA:D (2:1) samples respectively, add them into 10 mL of phosphate buffer of pH 1.2-7.2 to form a supersaturated solution, and set the temperature at 37 °C and a speed of 200 r / min. -1 The samples were taken out and filtered to obtain the sample solutions for later use. The content of each sample was measured by ultraviolet spectrophotometer at 288 nm, 248 nm, 244 nm and 242 nm, and the solubility of each sample at different pH was calculated, and statistical analysis was performed using Origin 8.0.
[0223] The solubility of UA, D and different UA eutectics under different pH conditions is as follows Fig.52 shown.
[0224] Depend on Fig.48 Analysis shows that as the pH value increases from 1.2 to 7.2, the solubility of UA:D2:1(DCM) increases with the pH value, and the solubility of the cocrystal is maximum at pH 7.2, which is 5 times the solubility of UA at this pH value.
[0225] Depend on Fig.49 Analysis shows that as the pH value increases from 1.2 to 7.2, the solubility of the UA:D (2:1) eutectic does not change significantly with the increase in pH value, and under various pH conditions, the solubility of UA:D (2:1) is slightly greater than that of UA, but less than that of D, indicating that the solubility of the prepared UA:D (2:1) eutectic has not been significantly improved.
[0226] Comparing the solubility of each group, the results show that in the pH range of 1.2-7.2, the solubility of different UA cocrystals increased several times, and it was statistically significant. After the preparation of UA:D2:1(DCM) and UA:D(2:1)UA cocrystals, the solubility was improved to varying degrees compared with UA, among which UA:D2:1(DCM) had the best solubility improvement.
[0227] 2. In vitro dissolution assay
[0228] 1) Establishment of working curve
[0229] (1) Preparation of UA solution: Accurately weigh 1.0 mg of UA into a 25 mL volumetric flask and add pH 7.2 phosphate buffer to a concentration of 40 μg mL -1 UA solution was diluted to 36, 32, 28, 24, 20, 16, and 8 μg mL -1 For a series of solutions, measure the absorbance values and draw a standard curve with concentration as the horizontal axis and absorbance ABS as the vertical axis.
[0230] (2) Preparation of ligand D solution: Accurately weigh 1.0 mg of D into a 25 mL volumetric flask and add pH 7.2 phosphate buffer to a concentration of 40 μg mL -1 Solution D was diluted to 36, 32, 28, 24, 20, 16, and 8 μg mL -1 For a series of solutions, measure the absorbance values and draw a standard curve with concentration as the horizontal axis and absorbance ABS as the vertical axis.
[0231] (3) Preparation of UA eutectic solution: Accurately weigh 1.0 mg of UA:D2:1 (DCM) into a 25 mL volumetric flask and add pH 7.2 phosphate buffer to a concentration of 40 μg mL -1 UA solution was diluted to 36, 32, 28, 24, 20, 16, and 8 μg mL -1 For a series of solutions, measure the absorbance values and draw a standard curve with concentration as the horizontal axis and absorbance ABS as the vertical axis.
[0232] 2) Determination of in vitro dissolution and oil-water partition coefficient
[0233] Accurately weigh appropriate amounts of UA, D, UA:D2:1 (DCM), and UA:D (2:1) samples into a dialysis bag (MWCO 3500), add 10 mL of purified water containing 1% Tween 80, and incubate at 37 °C and 150 r / min. -1 Under constant temperature and oscillation conditions, 3 mL of samples were taken at 1, 2, 4, 6, 8, 10, and 12 h, and 3 mL of the same dissolution medium at the same temperature was added in time. The absorbance values were measured at wavelengths of 288 nm, 248 nm, 244 nm, and 242 nm, and the data were recorded. The cumulative dissolution percentage F (%) of each sample was calculated according to Formula 3, and the time-cumulative dissolution curve was drawn.
[0234]
[0235] Where: W: total amount of drug added (mg)
[0236] M i (Mj ): Concentration measured at the i-th (j-th) sampling time (mg·mL -1 )
[0237] i, j = 1, 2, 4, 6, 8, 10, 12 (corresponding time is 1h, 2h, 4h, 6h, 8h, 10h, 12h)
[0238] The classic shake flask method was used, with n-octanol as the oil phase (O) and deionized water as the water phase (W). The mixture was placed in a separatory funnel with an oil-water ratio of 4:1 and shaken overnight to saturate the oil-water phase. Excess UA, D, UA:D2:1 (DCM), and UA:D (2:1) samples were added to the separatory funnel and stirred at (37±0.5)℃ and a rotation speed of 150 r·min. -1 The mixture was placed in a constant temperature oscillator for 36 hours under the same conditions, and then taken out and allowed to stand for stratification, and the oil phase and the water phase were separated and stored separately for later use. The oil phase and the water phase were diluted to appropriate times, and the absorbance values were measured at wavelengths of 288nm, 248nm, 244nm, and 242nm, and the data were recorded. The drug concentration in the oil phase and the drug concentration in the water phase were calculated. According to the formula: P = 4*Co / Cw (where: P is the oil-water partition coefficient, Co is the drug concentration in the oil phase, and Cw is the drug concentration in the water phase), the oil-water partition coefficient lgP of UA, ligands, and each UA eutectic was calculated.
[0239] The in vitro dissolution test results of UA, D, UA:D2:1 (DCM), and UA:D (2:1) cocrystals are shown in Fig.50 .
[0240] Depend on Fig.50 It can be seen that the in vitro cumulative dissolution rate of UA:D2:1(DCM) cocrystal increased compared with UA and ligand. At 12h, the cumulative dissolution rate of UA:D2:1(DCM) was 6 times that of UA, and the cumulative dissolution rate of UA:D(2:1) cocrystal did not improve significantly. The results show that UA can improve solubility and dissolution after forming a cocrystal with a suitable ligand.
[0241] 3 Determination results of oil-water partition coefficients of usnic acid and eutectic samples
[0242] The calculation results of the oil-water partition coefficient of UA and UA cocrystal are shown in Table 3.8. The lg P values of UA:D2:1(DCM) and UA:D(2:1) are 2.75±0.04 and 2.74±0.04, respectively. Compared with the lg P value of UA of 2.89±0.01, the oil-water partition coefficient of UA cocrystal is reduced, indicating that the percutaneous permeability of UA will be improved after the formation of cocrystal.
[0243] Table 3.8 Oil-water partition coefficients of different usnic acid eutectics (n=3)
[0244]
[0245] Combined with the results of solubility, in vitro dissolution and oil-water partition coefficient investigation, UA and UA:D2:1 (DCM) were selected for further in vitro permeation experiments. The results of in vitro cumulative permeation percentage are shown in Table 4.9. The zero-order reaction equation, first-order reaction equation and Higuchi equation were fitted. The results are shown in Table 4.10. Origin 8.0 was used to draw the in vitro cumulative permeation rate of UA and each UA cocrystal, as shown in Table 4. Fig.51 shown.
[0246] Table 3.9 Cumulative transdermal dose of UA and UA co-crystal (n=3)
[0247]
[0248] Table 3.10 In vitro transdermal equation fitting
[0249] drug Zero-order reaction equation <![CDATA[R 2 Value]]> First order reaction equation <![CDATA[R 2 Value]]> Higuchi reaction equation <![CDATA[R 2 Value]]> UA y=3.58+0.5x 0.9435 <![CDATA[y=13.87(1-e -0.13x )]]> 0.8625 <![CDATA[Y=2.7x 1 / 2 +0.91]]> 0.9953 UA:D2:1(DCM) y=4.62+0.648x 0.9773 <![CDATA[y=22.42(1-e -0.080x )]]> 0.6479 <![CDATA[y=3.27x 1 / 2 +1.08]]> 0.9004
[0250] As shown in Figure 3.9, the cumulative penetration of UA is 716.88±113.65μg / cm 2 The cumulative permeation of UA:D2:1(DCM) in 24 h was 1031.40±214.13μg / cm 2 Compared with the cumulative permeation of UA in 24 h, UA:D2:1(DCM) increased by 1.44 times, indicating that UA eutectic is significantly superior to UA in permeation performance.
[0251] The in vitro permeation equation was fitted. It can be seen from Table 3.10 that the in vitro permeation behavior of UA conforms to the Higuchi reaction equation; the in vitro permeation behavior of UA:D2:1 (DCM) conforms to the zero-order reaction equation.
[0252] Example 5 Investigation of the antibacterial activity of usnic acid cocrystal
[0253] 1. Activation of bacterial strains and determination and drawing of growth curves
[0254] Take the seed solution of each strain and transfer it to a conical flask containing 100 mL of liquid culture medium at a 2% inoculation rate. After shaking, place it in a 37°C, 150 r·min incubator. -1 Culture at constant temperature, take 3 mL of the mixture at 0, 1, 2, 4, 6, 8, 10, 12, 16, 20, and 24 h, and use sterile culture medium as blank control to measure its OD 600 The growth curve was drawn with OD value as the ordinate and culture time as the abscissa.
[0255] 2. Solution preparation
[0256] Accurately weigh appropriate amounts of UA and D, add 5 mL of DMSO to dissolve, then add an equal volume of purified water and shake well to obtain 1280 μg mL -1 The solution was stored at 4°C for future use.
[0257] Accurately weigh 12.8 mg of UA:D2:1 (DCM) and UA:D (2:1) cocrystals, add 5 mL of DMSO to dissolve, then add an equal volume of purified water and shake well to obtain 1280 μg mL -1 The solution was stored at 4°C for future use.
[0258] 3. Determination of MIC of usnic acid, ligand and cocrystal
[0259] Dilute the bacterial solution to 5×10 5 CFU·mL -1 Use the microbroth dilution method to dilute the solution in equal proportions to obtain a series of concentrations of 640, 320, 160, 80, 40, 20, 10, 5, 2.5, 1.25, and 0.625 μg mL -1 , the schematic diagram is as follows Fig.52 Staphylococcus aureus and MRSA were cultured in a shaking incubator at 37°C for 20 h, while Candida albicans and Malassezia were cultured in a shaking incubator at 35°C for 36 h and the OD values were measured. 600 , calculation formula 5 is as follows, perform 3 parallel experiments, record the results, and calculate the MIC of each sample.
[0260]
[0261] Determine the OD of the bacterial solution at each time point 600 Value, see the result Fig.53 .
[0262] Depend on Fig.53 It can be seen that the logarithmic growth period of Staphylococcus aureus and MRSA is 2 to 8 hours, the logarithmic growth period of Candida albicans is 6 to 12 hours, and the logarithmic growth period of Malassezia is 8 to 16 hours. According to the actual operating conditions, the shaking incubation time of Staphylococcus aureus and MRSA is selected as 6 hours; the shaking incubation time of Candida albicans and Malassezia is selected as 10 hours.
[0263] The in vitro antibacterial results of each group of samples are shown in Table 4.3.
[0264] Table 4.3 MIC concentrations of different usnic acid cocrystals
[0265]
[0266] As shown in the table, the MIC values of usnic acid against Staphylococcus aureus, MRSA, Candida albicans, and Malassezia are 20, 20, 640, and 160 μg·mL, respectively. -1The calculated MIC concentrations of D against Staphylococcus aureus, MRSA, Candida albicans, and Malassezia were 320, 320, 320, and 160 μg·mL, respectively. -1 The results showed that the MIC value of UA:D 2:1 (DCM) and UA:D (2:1) cocrystals against Candida albicans was reduced by 320 μg·mL -1 The MICs of UA against the other three bacteria were the same as those of UA.
[0267] Example 6 Investigation of the anti-inflammatory and wound repair activities of usnic acid cocrystal
[0268] 1. Preparation
[0269] PEG400:PEG4000 were mixed in a ratio of 4.3:0.7, heated and melted to form an ointment base. Appropriate amounts of UA, D, and UA:D2:1 (DCM) eutectic were accurately weighed, added to the ointment base and mixed evenly. After homogenization, 10 mg·10 g -1 Medicinal ointment of the specified specifications, keep on hand.
[0270] 2. Animal experiments
[0271] After 5 days of adaptive feeding, 80 Kunming mice were randomly divided into 10 groups (n=8), namely normal group, control group, model group, UA group, D group, UA:D2:1 (DCM) (DDCM) group, and positive drug group (Bactroban ointment). Except for the normal group, after routine disinfection and anesthesia, a 0.5 cm × 0.5 cm wound was prepared on the back of the mice after shaving the hair according to the full-thickness incision method, and 10 drops of ... 9 CFU·mL -1 The wound infection model was created by applying 20 μL of Staphylococcus aureus liquid with a concentration of 6.6 mg kg. The control group was smeared with normal saline, and the experimental groups were smeared with corresponding ointments for treatment. -1 After 14 days of drug administration, the weight and health status of the mice were recorded every day, and photos were taken to record the wound healing status.
[0272] After recording all data on the 15th day, the animals were killed, serum was taken for ELISA test, and the internal organs and back wound skin of each group of animals were removed, washed with physiological saline, grouped and numbered, and stored in 4% paraformaldehyde universal tissue fixative at 4°C for future use.
[0273] After 14 consecutive days of administration, blood was collected from the eyeballs and collected in heparin sodium blood collection tubes, then centrifuged at 4°C to obtain the supernatant. Samples (or standard products), primary antibody working solution, enzyme-labeled antibody working solution, and substrate working solution were added, and the stop solution was added after the reaction. The optical density (OD) value of each sample was measured at 450nm by a microplate reader, and the TNF-α, IL-6, and IL-10 content in serum was calculated based on the standard curve.
[0274] The weight change curves of mice in each group were drawn. The results are shown in Fig.54 The results show that the weight of mice remained basically stable, so the administration of drugs in each group did not affect the weight of mice.
[0275] Depend on Fig.55 It can be seen that after 14 days of continuous administration, the wounds of mice in each group were basically healed. The wounds of mice in each group were observed every day. It was found that the model group mice still had a small amount of exudate on the 3rd day, and some wounds still existed after 14 days of administration; the wounds of the positive drug group (Bactroban) and the control group were dry, and the wounds of the control group were basically healed after 12 days. There was no obvious wound in the UA group after 14 days of administration, and it was basically healed, confirming that UA has the effect of antibacterial and promoting wound healing. The wounds in the D group can be clearly seen to be reduced. Compared with the model group, the wounds of mice in the UA:D2:1 (DCM) UA cocrystal drug group were significantly reduced. There was no obvious wound at 12 days. The base was red and congested in the center of the wound. A small amount of granulation tissue had been newly formed. Thinner new skin could be observed, and the healed skin was smooth.
[0276] The morphology of regenerated skin tissue of rats in each group at different time points was shown in Fig.56 . As can be seen from the figure, on the 14th day of continuous administration, a large amount of collagen fibers were secreted in the Control group. The collagen fibers were not tightly and orderly arranged and distributed in the new dermis. No skin appendages were seen. Obvious signs of microvascular tissue healing were observed. In the sham operation infection group, the skin healing process was slow, and most of it was filled with inflammatory exudates. A large number of fibroblasts and a small number of collagen fibers were still seen in the dermis, and the epidermis was also thin. The epidermis in the UA group healed faster and was similar to the epidermis structure of normal skin. A small number of fibroblasts were seen in the new dermis, and a large number of collagen fibers were tightly arranged. Skin appendages in the differentiation stage were also seen. In the D group, the collagen fibers were not tightly and orderly arranged and distributed in the new dermis. No skin appendages were seen. In the Drug group, the epidermis healed, and a small number of fibroblasts were seen in the new dermis, and a large number of collagen fibers were tightly arranged. The epidermis in the UA:D2:1(DCM)(DDCM) group healed faster, with a small number of fibroblasts visible in the new dermis, and a large number of tightly arranged collagen fibers. Skin appendages were also visible, which were similar to the epidermis structure of normal skin. The above results show that UA and UA:D2:1(DCM) cocrystals promote the wound repair process.
[0277] The levels of pro-inflammatory factors TNF-α, IL-6 and anti-inflammatory factor IL-10 in the serum of each group were detected and plotted using Origin 8.0. The results are shown in Tables 5.3 and Figure 57-59Compared with the control group, the levels of serum TNF-α, IL-6, and IL-10 in the model group were significantly increased (p<0.01). Compared with the model group, the levels of IL-6 and TNF-α in the UA group were significantly decreased (P<0.01, P<0.001), and the level of IL-10 was slightly increased, with no significant difference (P>0.05); the levels of IL-6 and TNF-α in UA:D2:1(DCM) were significantly decreased (P<0.001), and the level of IL-10 was slightly decreased, but there was no significant difference (P>0.05); the levels of TNF-α, IL-6, and IL-10 in the D group and the positive drug group (drug group) were all decreased, with no significant difference (P>0.05). Compared with the drug group, the levels of IL-10, IL-6, and TNF-α in the UA:D2:1(DCM) and UA groups were slightly increased, with no significant difference. Therefore, it was judged that UA and UA cocrystal played an anti-inflammatory role by inhibiting the secretion of pro-inflammatory factors IL-6 and TNF-α, promoting wound repair, among which UA:D2:1 (DCM) had the best effect.
[0278] Table 5.3 Detection of pro-inflammatory factors TNF-α, IL-6 and anti-inflammatory factor IL-10 levels in serum of each group
[0279] Group IL-10 IL-6 TNF-α normal 1052.04±121.28 <![CDATA[25.77±3.08*** ### ]]> 38.12±0.93*** control 1057.39±35.95 15.70±2.41 46.25±3.40 model 1202.36±26.74 <![CDATA[23.83±3.36 ### ]]> <![CDATA[66.17±11.37 ### ]]> drug 1120.92±17.39 4.55±1.75 38.67±4.85 D 1126.73±26.58 <![CDATA[22.66±2.69 ### ]]> 34.36±0.92 UA 1272.72±61.86 13.77±2.91** 42.45±3.38*** UA:D2:1(DCM) 1138.57±92.33 14.16±2.00*** 40.83±4.08***
[0280] Note: Compared with the model group, *P<0.05; **P<0.01; ***P<0.001; compared with the drug group, # P < 0.05; ## P < 0.01; ### P<0.001.
Claims
1. A usnic acid-desonide cocrystal, characterized in that: The main drug component of usnic acid-desonide cocrystal is usnic acid, and the ligand component is desonide; the stoichiometric ratio of usnic acid to desonide is 2:1, and the XRD spectrum of the usnic acid-desonide cocrystal is shown in Figure 38.
2. The method for preparing the usnic acid-desonide cocrystal according to claim 1, characterized in that: The solvent evaporation method is used to prepare usnic acid-desonide cocrystals; the solvent evaporation method is used to prepare usnic acid-desonide cocrystals, which comprises the following steps: 1) Accurately weigh the main drug usnic acid and each ligand according to the stoichiometric ratio and add them into the reaction bottle; 2) Add solvent, stir thoroughly with magnetic stirring to dissolve, filter, and collect the filtrate in a vial; 3) Evaporating at room temperature to obtain usnic acid drug co-crystal; Step 2) The solvent is dichloromethane.
3. Use of the usnic acid-desonide co-crystal according to claim 1 in the preparation of antibacterial preparations.
4. Use of the usnic acid-desonide co-crystal according to claim 1 in the preparation of anti-inflammatory preparations.
5. Use of the usnic acid-desonide co-crystal according to claim 1 in the preparation of skin wound repair preparations.
Citation Information
Patent Citations
External preparation for improving transdermal absorption of usnic acid and application of external preparation to promotion of skin injury healing
CN106943341A
Treatment of inflammatory disease using ingestible device to release immune modulator
CN111225686A